Analysis of Job Satisfaction and Organizational Commitment to Positive Work Behavior of Employes - Yumardi; Ratno Adrianto; Irfansyah Baharuddin Pakki (Indonesian Journal of Global Health Research, 2026)
The main problems faced by hospitals in Indonesia from an internal perspective are the lack of human resource commitment, inconsistent organizational systems and leadership, differing perceptions regarding service quality, limited funds, and a lack of work culture. The purpose of this study is to identify the relationship between job satisfaction dimensions and organizational commitment dimensions and positive work behavior of employes at Kudungga Sangatta Regional General Hospital. The type of research used an observational cross-sectional quantitative research method, conducted over 3 months. The total sample size was 158 employes. The population in this study consisted of all employes in the support services department across 12 (twelve) installations or units at Kudungga Sangatta Hospital. Data collection techniques and research instruments are interviews and questionnaires. Data analysis is done using statistical tests, namely: Chi-Square test with a significance level of α= 0.05, and multiple logistic regression test. The conclusion from the 7 dimensions of independent variables that are related to positive work behavior of employes is job characteristics (p=0.000), rewards (p=0.000), work environment (p=0.000), and relationships with management (p=0.010), while those that are not related to positive work behavior of employes are affective commitment (p=0.518), continuance commitment (p=1.000), normative commitment (p=0.861), and the most dominant influence on positive work behavior of employes at Kudungga Sangatta Regional General Hospital is the rewards dimension with an Odd Ratio value of 7.338. It is recommended that efforts to improve the quality of hospital services by increasing employe job satisfaction include proportional recognition and attention, managing job characteristics to align with employe competencies and capacities, and creating a good work environment that can motivate employes and increase the intensity of management communication by involving employes in formal activities or joint events outside of office hours.